THE IMPORTANCE OF WATER AND THE IMPACTS OF POLLUTION: AN EDUCATIONAL ACTION IN A PUBLIC SCHOOL (CIPEEX, 2025)
Introduction: Water is an essential resource for sustaining life but faces increasing threats from pollution, which compromises its availability and quality. In this context, it is necessary to promote educational actions that foster environmental awareness from childhood. Through Resolution No. 13/2022, UniEvangélica institutionalized the curricularization of extension, allocating 10% of undergraduate course hours to extension activities that connect students with society. This report describes an educational intervention on the importance of water and the impacts of pollution carried out in a public school.Objective: To raise children’s awareness about the value of water for life on the planet and the harmful effects of pollution, encouraging critical reflection and proactive attitudes in defense of the environment.Method: The activity was conducted with students aged 7 to 9 from Luiz Carlos Bizinoto School. Active and playful methodologies were employed, including the production of drawings, the construction of a homemade filter, and the simulation of pollution effects. These practices encouraged children’s participation and facilitated their understanding of the concepts addressed.Discussion: The results highlighted the importance of adapting communication and using active methodologies to engage young audiences. The experience was based on Freirean principles, promoting dialogue and the exchange of knowledge between medical students and schoolchildren. Despite initial challenges, such as communication barriers, the establishment of trustful relationships contributed to overcoming these difficulties. The activity reinforced the role of university extension in shaping more empathetic, reflective professionals capable of communicating effectively with diverse audiences.Conclusion: The extension activity proved to be an effective strategy to integrate theory and practice, contributing both to the comprehensive education of university students and to the environmental awareness of children. The experience demonstrated the transformative potential of educational initiatives in strengthening environmental consciousness and fostering sustainable practices from the early school years.
Keywords: Environmental Education; Health Education; Extension; Schools